Upaya Pengelolaan Sampah Demi Mewujudkan Keberlanjutan Lingkungan - Praningtyas, Elisabeth Ria Viana; Sylvana, Andi; Jamaludin, Jamaludin; Subekti, Rini; Romadhani, Sahrul (Abdimas Indonesian Journal, 2024)
Senang Hati Village is a village resulting from the expansion located in Lebak Regency. As a new village, Senang Hati Village has homework that must be completed immediately, namely waste management. Senang Hati Village does not yet have good waste management so that the surrounding environment tends to be polluted and it is difficult to achieve environmental sustainability. The FEB UT PkM Team chose Senang Hati Village as a place to carry out PkM activities to help improve waste management. The implementation method is carried out in four stages. The results of the activity show that there is better waste management by this village. Garbage is no longer scattered on the side of the road, pooling in rivers, or piling up in yards so that the environment in the Senang Hati Village area is of better quality.